New Methods with Capped Options for Pricing American Options - Dongya Deng; Cuiye Peng (Journal of Applied Mathematics)
We propose two new methods: improved binomial methods and improved least square MonteCarlo methods (LSM), for pricing American options. These two methods are developed using the nice capped options which have closed-form formulas. Numerical examples are provided to verify that these two new methods are pretty efficient.